Establishment of Carotid Artery Dissection and MRI Findings in a Swine Model - Peng, Jing; Wu, Min; Doycheva, Desislava Met; He, Yi; Huang, Qiongzhen; Chen, Wei; Matei, Nathanael; Ding, Jun; Chen, Kangning; Xu, Ningbo; Zhou, Zhenhua (Frontiers in Neurology, 2021)
Carotid artery dissection (CAD) is the leading cause of ischemic stroke in young patients; however, the etiology and pathophysiology of CAD remain largely unknown. In our study, two types of dissections (length × width: 1.5 cm × 1/3 circumference of intima, Group I, n = 6; or 1.5 cm × 2/3 circumference of intima, Group II, n = 6) were created between the media and intima. Ultrasound (within 2 h after dissection) showed a dissociated intima in the lumen and obstructed blood flow in the surgical area. Digital subtraction angiography (DSA, 72 h after dissection), magnetic resonance imaging (MRI, 72 h after dissection), and hematoxylin–eosin (H&E, 7 days after dissection) staining confirmed stenosis (33.67 ± 5.66%) in Group I and total occlusion in Group II. In 10 out of 12 swine, the CAD model was established using a detacher and balloon dilation, and morphological outcomes (stenosis or occlusion) after CAD were determined by the size of intimal incision.